2019
DOI: 10.1002/glia.23607
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in the oligodendrocyte lineage: Plasticity or heterogeneity?

Abstract: Heterogeneity is a widely recognized phenomenon within the majority of cell types in the body including cells of the central nervous system (CNS). The heterogeneity of neurons based on their distinct transmission modes and firing patterns has been recognized for decades, and is necessary to coordinate the immense variety of functions of the CNS. More recently, heterogeneity in glial cells has been identified, including heterogeneity in oligodendrocyte progenitor cells (OPCs) and oligodendrocytes. OPC subpopula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 61 publications
3
66
0
Order By: Relevance
“…Our data demonstrate cell type-specific dynamics of myelination plasticity, even when the distinct neuronal subpopulations are interconnected within the same circuit, surrounded by a shared environment, and myelinated by a common set of oligodendrocytes. The cell type-specificity of myelin plasticity observed here could potentially be related to the bias for inhibitory axons displayed by a subset of the oligodendrocytes in V1 17 , or to a more general heterogeneity in the glia population 36 . An alternative, but not mutually exclusive, explanation might be that transcriptionally-distinct classes of neurons display different molecular signatures, such as cell surface markers, to individualize interactions with oligodendrocytes.…”
Section: Md-induced Remodeling Of Pv + Interneuron Axons Is Independementioning
confidence: 92%
“…Our data demonstrate cell type-specific dynamics of myelination plasticity, even when the distinct neuronal subpopulations are interconnected within the same circuit, surrounded by a shared environment, and myelinated by a common set of oligodendrocytes. The cell type-specificity of myelin plasticity observed here could potentially be related to the bias for inhibitory axons displayed by a subset of the oligodendrocytes in V1 17 , or to a more general heterogeneity in the glia population 36 . An alternative, but not mutually exclusive, explanation might be that transcriptionally-distinct classes of neurons display different molecular signatures, such as cell surface markers, to individualize interactions with oligodendrocytes.…”
Section: Md-induced Remodeling Of Pv + Interneuron Axons Is Independementioning
confidence: 92%
“…In support of this idea, it has been shown that laminin‐2/merosin is present on only a subset of axons in the CNS (Colognato et al, ) and that just some subtypes of neurons modulate myelination by signals that are released along their axons (Koudelka et al, ). In light of the increasing recognition of OLG heterogeneity (Dimou & Simons, ; Foerster, Hill, & Franklin, ; Marques et al, ; Ornelas et al, ; Spitzer et al, ; Trotter & Mittmann, ; van Bruggen, Agirre, & Castelo‐Branco, ), one might postulate that different OLG subtypes may respond in an individual fashion to the various cues provided by subpopulations of axons. It should be noted here that current knowledge related to the role of the OLG growth cone and its actin cytoskeleton during OLG differentiation and the initiation of myelination is still rather limited.…”
Section: The Growth Cone and Its Actin Cytoskeleton As A Driver Of Dymentioning
confidence: 99%
“…Ultimately, these two populations of OPCs display similar properties (Marques et al, ; Tripathi et al, ) and both differentiate to form the myelinating cell of the central nervous system (CNS), the oligodendrocyte. However, there is some heterogeneity during adulthood in the electrophysiological properties of OPCs depending on the region of the CNS in which they are located (Foerster, Hill, & Franklin, ; Spitzer et al, ; van Bruggen, Agirre, & Castelo‐Branco, ).…”
Section: Introductionmentioning
confidence: 99%